THE INFLUENCE OF EMPLOYEE COMPETENCE AND ORGANIZATIONAL ADAPTABILITY ON HUMAN RESOURCE READINESS IN IMPLEMENTING THE TRANSFER OF SUPERVISION OF FINANCIAL DERIVATIVE PRODUCTS AND FOREIGN EXCHANGE MARKETS FROM BAPPEBTI TO OJK - Rio Ramadhani; Zulkifli Rangkuti; Hadi Purnomo (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to analyze the influence of employee competency and organizational adaptability on human resource readiness in implementing the transition process of supervision of financial derivative products and the foreign exchange market from the Commodity Futures Trading Regulatory Agency (BJB) to the Financial Services Authority (OJK). The research problem is motivated by the importance of human resource readiness in facing changes in the supervisory system, regulations, and inter-agency working mechanisms that have the potential to affect the effectiveness of financial sector supervision. This study uses a quantitative method with an associative approach. Data collection was conducted by distributing questionnaires to employees related to the supervision process of financial derivative products and the foreign exchange market. Data analysis techniques used validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results show that employee competency and organizational adaptability have a positive and significant effect on human resource readiness, both partially and simultaneously. This finding indicates that improving employee capabilities, organizational support, and the ability to adapt to policy changes are important factors in supporting the success of the supervisory transition process. The implications of this study are expected to be considered by relevant institutions in designing human resource development strategies and organizational strengthening during the transition period of supervisory authority.